Business Model Design Themes, Value Propositions and Firm Performance - Ekaterina Migol; Olga Tretyak; Anna B Holm (Journal of Business Models, 2018)
This paper presents the results of a study of business model design themes of 30 retailers from Russia. We find a positive relationship between novelty-centred business models and company performance. Furthermore, companies achieved the best performance by combining elements of the efficiency and complementarity business model design themes.